Incorporating Archaeology Into Local Government Historic Preservation and Planning: A Review of Current Practice. Issue 2 (2nd April 2016) - Deur, Douglas; Butler, Virginia L.
Abstract : Problem, research strategy, and findings: The fate of archaeological sites in cities, towns, and county jurisdictions are greatly affected by the decisions of local governments and planning departments, which usually operate with little formal guidance regarding archaeological site stewardship. What strategies do local governments use to effectively manage archaeological sites in their jurisdictions? Which ones work best? To address these questions, we carried out an exploratory study of mechanisms used by local government planners for archaeological resource protection in 24 states between 2008 and 2015, obtaining information from 69 local governments. We use questionnaires and interviews with local government staff, Tribal Historic Preservation Officers (THPOs), and State Historic Preservation Officers (SHPOs),  identifying the range of practices employed. Within the jurisdictions we studied, the most elaborate programs a) have local ordinances protecting archaeology, on-staff archaeologists, and use special archaeological districts and zoning overlays, survey, and development guidelines linked to archaeological site probability models; b) maintain cost-saving partnerships with SHPOs, THPOs, universities, and local nonprofit heritage organizations; c) or use a combination of these practices. Takeaway for practice: Virtually all local governments possess archaeological resources and an archaeological heritage worthy of protection. Local site preservation is most effective when it moves from project-based compliance to become an integral part of the overall planning process. By protecting these places and educating the public regarding their importance, local governments help to bolster local economies, local pride, and local amenities in a way that benefits residents, tourists, and generations to come.